The right to the environment? Article 4(1) of the Polish Environmental Protection Law Act from a combined comparative law and Polish-English legal translation perspective - Kusik, Przemysław (Comparative Legilinguistics, 2023)
A human right to the environment is increasingly recognised in both domestic and international law. Also in Polish legal scholarship, there is a discussion over the possibility of deriving a right to the environment from the Constitution or ordinary statutes, including Article 4(1) of the Environmental Protection Law Act. The existing English translations of its opening words, and specifically the term powszechne korzystanie ze środowiska, appear to mirror the legal controversy. Compared to Poland, the major common law jurisdictions, i.e. England and the USA, show multiple differences in respect of the public’s enjoyment of the environment. In addition to a distinct legal mentalité, grounded on a case-by-case approach, negative freedoms and remedies thinking, both jurisdictions are characterised by considerable private ownership of natural resources like rivers and forests. In view of this legal and translation problem, the present paper seeks to employ comparative law methodology to establish an acceptable English translation equivalent of the term powszechne korzystanie ze środowiska. The analysis is also an attempt to go beyond the ways in which the use of comparative law in legal translation is typically perceived, i.e., beyond functionalism, beyond micorcomparison and beyond conceptual analysis.